Pacifism and Jihad - Farah Ramin (Religious Inquiries, 2020)
In the present era, theorists try to explain the phenomenon of peace in the world through political theories, one of which is pacifism. Anti-war pacifism is considered the most common type of pacifism, because war is one of the main issues in international diplomacy. In this study, the initial aim is to provide a general overview of pacifism and its types, including virtue pacifism, deontological pacifism, consequential pacifism, and peacemaking, in international arena and then to introduce a different notion of peace-making based on Islamic diplomacy and to argue for a type of peace-making called perpetual peace. The findings of this study show that in Islam peace does not always mean the absence of violence but rather ever-lasting peace that flourishes in the absence of oppression, injustice, corruption, and tyranny.